2020
DOI: 10.1111/jcmm.15519
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Gadd45β ameliorates the inflammation and renal fibrosis caused by unilateral ureteral obstruction

Abstract: The growth arrest and DNA damage‐inducible beta (Gadd45β) protein have been associated with various cellular functions, but its role in progressive renal disease is currently unknown. Here, we examined the effect of Gadd45β deletion on cell proliferation and apoptosis, inflammation, and renal fibrosis in an early chronic kidney disease (CKD) mouse model following unilateral ureteral obstruction (UUO). Wild‐type (WT) and Gadd45β‐knockout (KO) mice underwent either a sham operation or UUO and the kidneys were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Dual-Specificity Phosphatase 1 (DUSP1), one of the enzymes for mitogen-activated protein kinases (MAPKs), plays a key role of initiating MAPK cascade ( Li et al, 2021 ). Growth Arrest and DNA Damage Inducible Beta (GADD45B) is also often implicated in the pathogenesis of CKD ( Moon et al, 2020 ). GADD45B serves as an anti-apoptotic factor, exerting its effects by directly binding to MKK7.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-Specificity Phosphatase 1 (DUSP1), one of the enzymes for mitogen-activated protein kinases (MAPKs), plays a key role of initiating MAPK cascade ( Li et al, 2021 ). Growth Arrest and DNA Damage Inducible Beta (GADD45B) is also often implicated in the pathogenesis of CKD ( Moon et al, 2020 ). GADD45B serves as an anti-apoptotic factor, exerting its effects by directly binding to MKK7.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, GADD45b is a critical regulator of autoimmunity (72) that plays an important role in B cell apoptosis in response to Fas stimulation through activation of NF-kB (73). A recent report suggests that ablation of GADD45b ameliorates the inflammation and renal fibrosis caused by unilateral ureteral obstruction (UUO) in a chronic kidney disease mouse model (74). Previously it was shown that GADD45b was also induced in CD4 + T cells by inflammatory cytokines, such as IL-12 and IL-18 (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…The colon, ileum, and liver tissues were cut at 5 μm thickness and stained separately with hematoxylin and eosin (H&E), similar to a previous study [ 23 , 24 ]. The severity of colitis was blindly assessed by a pathologist and scored using the histological scoring method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%